Online news and gamification habits in late adulthood: a survey with older adults - Regalado, Francisco (2021)
Older adults are becoming to comprise a significant proportion of the global population. Simultaneously, the use of technologies by this age group is growing at a fast pace. However, technological products still lack attention to older adults’ physiologic, psychologic, and social needs. Journalism is a significant part of one’s lives, as it allows to be always up to date with the World’s events, and which was not left behind in this World’s cyberization process. In a reality where everything shouts for the users’ attention, gamification – i.e. the use of game elements and its logics for contexts that go beyond entertainment purposes – presents itself as a way to capture users’ motivations, possibly leading them to use products in a consistent and systematic way. The aim of this paper is to describe a survey conducted from June of 2020 until the first week of July of 2020, to a total of 248 older adults aged 50 and over from sixteen different countries. During this study, researchers intended to assess older learners’ context in terms of social media, online news, and games usage, as well as their familiarity with gamification strategies. The results suggest that the questionnaire’s respondents are online news consumers, with a heavy usage of computers to access the Internet. Additionally, it was possible to report the main activities respondents like to be valued for – activity in groups; frequency with which they talk to other people; and debate, share and react to news – allowing the design of a gamification system.